Laminar Convective Heat Transfer And Friction Factor Of AL2O3 Nanofluid In Circular Tube Fitted With Twisted Tape Inserts - Sharma, Korada Viswanatha; L. Syam, Sundar (Universiti Malaysia Pahang, 2011)
We experimentally investigated the fully developed laminar convective heat transfer and friction factor characteristics of different volume concentrations of Al2O3 nanofluid in a plain tube and fitted with different twist ratios of twisted tape inserts. Experiments were conducted with water and nanofluid in the range of 700 Re2200, particle volume concentration of 0.5%, and twisted tape twist ratios of 0H / D15. The nanofluid heat transfer coefficient is high compared to water and further heat transfer enhancement is observed with twisted tape inserts. The pressure drop increases slightly with the inserts, but is comparatively negligible. A generalized regression equation is developed based on the experimental data for the estimation of the Nusselt number and friction factor for water and nanofluid in a plain tube and with twisted tape inserts.